¿LA VINCULACIÓN EN AUSENCIA AL PROCESO PENAL VULNERA GARANTÍAS FUNDAMENTALES DEL PROCESADO? (2016)
In Colombia, against the inability of the state to appear personally to the alleged offender of the criminal law in order to link him to the investigation and be able to bring him to trial, it was decided to prosecute him in absence (in the case of not being able to locate him) , or in contempt (in the event that the person knows is being processed and do not want to undergo the procedure). This has shown that the advancement of criminal proceedings in the absence of the alleged offender can generate violations of fundamental rights and guarantees that, contrary to combat impunity, is a source of judicial mistakes, generating community distrust of the administration of justice. This document was prepared by the normative approach, turning to sources such as international law treaties, laws, codes, case law and doctrine, found in books, journals, and in the web.